Moving beyond storytelling emerging research in microfinance - Watkins, Todd A.; Hicks, Karen M., 1947- (Contemporary studies in economic and financial analysis, 2009)
Despite the promise for international development, despite the proven track record of exceptional loan repayment rates, and despite the development of competitive markets in countries like Bolivia, Peru and Bangladesh or the global expansion of microfinance access to tens of millions of new clients, little research has explored the impact this expansion has had on global poverty and economic and social development in general. To address this gap, this volume brings together leaders in the microfinance industry and researchers representing a range of academic disciplines. Our goal is to outline a multidisciplinary research agenda for the field. The topics addressed in this volume and the questions posed can serve to guide social scientists, technology experts, development specialists, investors, microfinance practitioners, policymakers and students.